Quantile treatment effects in the regression discontinuity design - Markus Frölich; Blaise Melly (Institute for the Study of Labor (IZA), 2008)
This paper shows nonparametric identification of quantile treatment effects (QTE) in the regression discontinuity design (RDD) and proposes simple estimators. Quantile treatment effects are a very helpful tool to characterize the effects of certain interventions on the outcome distribution. The distributional impacts of social programs such as welfare, education, training programs and unemployment insurance are of large interest to economists.
urn:nbn:de:101:1-20080820247
Keywords: C13; 330; Quantile treatment effect; causal effect; endogeneity; regression discontinuity; Regression; Nichtparametrisches Verfahren; Kausalanalyse; Theorie